New species and records of Sericini of India (Coleoptera: Scarabaeidae: Melolonthinae) II. - Bhunia, Debika; Gupta, Devanshu; Chandra, Kailash; Ahrens, Dirk (Zootaxa, 2021)
Here we present a new record of Microserica nicobarensis (Redtenbacher, 1868) and describe further two new species from India: Nepaloserica cheemaensis Bhunia, Gupta, Chandra & Ahrens new species, and Maladera reyaensis Bhunia, Gupta, Chandra & Ahrens, new species. Species morphology is described and illustrated, and their distribution is shown on a map.